A Systematic Review of the Effect of Climate Change on Rice Farming in Nepal - Bhusal, Tulsi Ram; Sinutok, Sutinee; Gyawali, Saroj (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Exponential increments of CO2 concentration and greenhouse gases in the atmosphere are causing climate change. Climate is an important factor in rainfall patterns and elevated air temperature and plays an important role in crop production. Rice is an important crop among Nepali farmers and adaptation is very crucial to cope with the climate change; however, due to lack of sufficient funds allocated in this sector, there is no intervention anymore from the government side in terms of policy. The climatic trends that are affecting the annual rice yield in Nepal are discussed thoroughly in this study. This study reviewed published studies from different indexing sources and sites and inferred some key points regarding the conditions of rice production in Nepal. Mainly due to increment of the average temperature, other physical conditions required for the proper cultivation of rice are changing. As a result, there has been a slight increment of annual rice production in the higher altitudes of Nepal where initially it was not possible to cultivate rice due to the colder climate. Moreover, the production of rice in lower altitudes has reduced. Although some farmers in the country have practiced different methods of cultivation to reduce the effect of climate change, a lack of available technology and financial support from government level has made it difficult for many of them to make necessary changes in rice production on their own. Therefore, with extensive research and an extension program, government officials and policy makers should concentrate on developing climate resilient adaptation measures for rice farming. This systematic study effectively presents the magnitude of the impact on rice farming due to changes in the climatic conditions in Nepal.